Patterns of Consumption and Potential Home Industry of Processed Fish Products in Kelurahan Bungus Barat - Hesty Parbuntari (Fakultas MIPA Universitas Negeri Padang, 2021)
The abundance of marine wealth in West Sumatra has not been maximally utilized even though the pattern of community fish consumption in West Sumatra has been declared to have increased in the last 10 years. This is caused by several factors such as inadequate management of the empowerment of marine and fisheries potentials, limited fishing and processing technology, and dependence on climate in Indonesia. Bungus is one of the areas in Padang City that has quite high fisheries resources. The composition of landed fish species is generally dominated by large pelagic species such as tuna, skipjack, cob, black stick and so on. Existing fishery products in the Kelurahan Bungus Barat include fresh fish and frozen fish. Non-export quality fresh fish products are distributed for public consumption in West Sumatra and the surrounding area. Export quality fish products are distributed to Japan and America. Based on the results of a questionnaire analysis to respondents in the West Bungus area, the conclusion obtained is that the community has a good pattern of fish consumption because of public awareness of fish nutrition besides the potential of the home industry of processed fish products in the Bungus Barat Village is also quite high because it is supported by the government and abundance of fish in the area.